HIV in the European Region : Vulnerability and Response - Platt, Lucy; Jolley, Emma; Hope, Vivian; Latypov, Alisher; Hickson, Ford; Reynolds, Lucy; Rhodes, Tim (World Bank, Washington, DC, 2014)
This report aims to describe the dynamics of HIV epidemics among vulnerable and key populations at high risk in the European region, focusing specifically on people who inject drugs (PWID), sex workers (SWs) and men who have sex with men (MSM). It does so in order to inform future HIV prevention, treatment and care responses as well as to guide future HIV prevention surveillance and research. In addition to a description of methods (below), the report comprises three main sections. Chapter 2 synthesizes evidence drawn from European HIV surveillance data (chapter 2.1) and targeted HIV prevalence studies (chapter 2.2). Chapter 3 synthesizes evidence drawn from systematic reviews of epidemiological studies among PWID (chapter 3.1), SWs (chapter 3.2) and MSM (chapter 3.3). Chapter 4 draws upon the evidence reviewed in Chapter 3 as well as the international literature more broadly to consider implications for strengthening responses, including in relation to HIV surveillance (chapter 4.1) and HIV prevention for PWID (chapter 4.2), SWs (chapter 4.3) and MSM (chapter 4.4). In chapter 5, the authors draw our conclusions.